Active Learning: The Dewey, Piaget, Vygotsky, and Constructivist Theory Perspectives - Pardjono Pardjono (Universitas Negeri Malang, 2016)
Active Learning Approach has long been implemented in Indonesian schools, and until now the implementation of Active Learning Approach remains to be suggested to improve the quality of learning process in Indonesian classrooms. However, the constraint is still on the definition of active learning itself. This article discusses the nature of Active Learning from the perspectives of four theories: Dewey's theory of progressive education, Piaget's theory of assimilation and accommodation, Vygotsky's theory of social context and zone of proximal development, and theory of constructivism. The discussion involves the nature of knowledge, learning, and teaching including the roles of teachers in active learning based on the four theories